Iatrogenic damage in restorative tooth preparation and management - Basudan, Thuraya Abdulrahim; Alghaythi, Khalid Shami; Abuhabshah, Ali Abdullah; Muhareb, Abdullah Khaled Bin; Alshahrani, Mastour Safar; Alabdulaziz, Noura Fahad; Algthaiae, Mohammed Saeed; Alzaidi, Maram Abdulshakur; Alandonisi, Alaa Mohammad; Alareshi, Maryam Talal; Bazuhair, Lama Mohammed (International Journal Of Community Medicine And Public Health, 2021)
Iatrogenic damage in restorative teeth preparation and management constitute a significant issue that dentists and surgeons might face during and after restoration procedures. Many presentations can be observed for the injured enamel following iatrogenic damage as the presence of fine scratches, 1 mm wide vertical grooves, extensive damage and indentations. Following the occurrence of such complications, subsequent changes to the properties of the affected areas can significantly increase the risk of developing dental caries. It is essential to shedding more light on such phenomena to increase awareness among dentists and physicians and to enhance the potential outcomes. Accordingly, in this literature review, the aim was to discuss the iatrogenic damage in restorative teeth preparation and management as per evidence from the current studies in the literature. At first, the discussion was around the different types of iatrogenic injuries based on the affected regions and the incidence of adjacent teeth injury during restoration was high. Moreover, it had been discussed the potential mechanisms and contributing factors that might flare up the injury and increase the risk of significant damage induction. Hypersensitivity and using rough materials are two common factors that may induce inflammation and induce damage. Further investigations might be needed for the implication of safe practices for surgeons and dentists to enhance the outcomes.